Medication adherence and associated factors toward antihypertensive medication in Western Rajasthan, India: A tertiary center study - Vishal Krishnan; Narendra Kumar Kaushik; Sudipta Pal; Ravinder Kumar; Gopal Singh; Shatrughan Pareek (MGM Journal of Medical Sciences, 2023)
Introduction: Hypertension is a form of cardiovascular disorder that results from a wide range of interconnected etiologies. Untreated and uncontrolled hypertension leads to structural and functional abnormalities of the cardiovascular system, ultimately harming the body’s vital organs, e.g., heart, kidneys, and brain. The study aimed to assess the prevalence of medication adherence among hypertensive patients. Materials and Methods: This study was conducted with a quantitative approach and descriptive research design. The study was conducted at the Outpatient Department of Medicine, Prince Bijay Singh Memorial Hospital & Associated Group Hospitals, Sardar Patel Medical College, Bikaner, Rajasthan, India. The population was 615 hypertensive patients. A nonprobability convenient sampling technique selected the participants. Data collection was done with the help of a demographic profile and Modified Morisky Medication adherence 8-scale. Results: In this study, most subjects (53.98%) were male. Approximately half of the participants (49.75%) had an average level of medication adherence, followed by 38.70% poorly adhering to their prescribed hypertensive regimens. The overall mean medication adherence score was 6.122 ± 1.539. In addition, variables such as age, educational status, other illnesses, regular visits to the doctor, and allergy to drugs were statistically (<0.05) associated with levels of medication adherence. However, gender, duration of illness, and residence were not statistically related to levels of medication adherence. Conclusion: Findings of the study highlighted that medication adherence was very low among hypertensive patients. Therefore, prompt actions are needed to enhance medication adherence among hypertensive patients, which may reduce hypertension-related morbidity and mortality.